A high-power lithium-ion hybrid capacitor based on a hollow N-doped carbon nanobox anode and its porous analogue cathode. Issue 43 (23rd October 2019) - Liang, Tian; Wang, Huanwen; Fei, Rixin; Wang, Rui; He, Beibei; Gong, Yansheng; Yan, Chunjie
Abstract : A novel "dual carbon" lithium-ion hybrid capacitor configuration is designed by using an anode of a hollow nitrogen-doped carbon nanobox and its porous analogue cathode. Abstract : Developing advanced lithium-ion hybrid capacitors (LIHCs) has a critical challenge of matching kinetics and capacity between the battery-type anode and the capacitive cathode. In this work, a novel "dual carbon" LIHC configuration is constructed to overcome such a discrepancy. Specifically, hollow nitrogen-doped carbon nanoboxes (HNCNBs) are synthesized by a simple template-assisted strategy. As an anode material (0.01–3 V vs . Li/Li + ), the HNCNB electrode exhibits high specific capacity (850 mA h g −1 at 0.1 A g −1 ) and superior rate capability (321 mA h g −1 at 20 A g −1 ). After alkaline activation, the HNCNBs become highly porous (PHNCNBs), which offers better capacitance performance within the potential window from 2.5 to 4.5 V ( vs . Li/Li + ) than commercial activated carbon (AC). Coupling a pre-lithiated HNCNB anode with a PHNCNB cathode forms a dual-carbon LIHC. Since the similar hollow structure in both electrodes could diminish the diffusion distance, the as-prepared HNCNB//PHNCNB LIHC provides high energy densities of 148.5 and 112.1 W h kg −1 at power densities of 250 and 25 000 W kg −1, respectively, together with long-term cycling stability, which efficiently bridges the gap between supercapacitors and lithium ion batteries. Furthermore, the self-discharge behavior and the temperature-dependent performance are also investigated.